Pengaruh EPS dan NPM terhadap Harga Saham - Robbi Wildan Fitra; Nursito Nursito (IPM2KPE, 2022)
This study aims to determine the effect of Earning Per Share (EPS) and Net Profit Margin (NPM) partially or simultaneously on Stock Prices in Pulp and Paper Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the 2015-2018 period. The research method used is descriptive verification with data analysis using Multiple Linear Regression analysis. The technique used to determine the sample in this study is purposive sampling and obtained 7 companies for 3 years of research. The results showed that the coefficient of determination (R2) was 0.553 or 55.3%. The value of Fcount > Ftable, which is Fcount of 16.572. In conclusion, partially or simultaneously EPS and NPM affect stock prices. Keywords: Earning Per Share (EPS), Share Price, Net Profit Margin (NPM)